Improved Performance of Serum Alpha-Fetoprotein for Hepatocellular Carcinoma Diagnosis in HCV Cirrhosis with Normal Alanine Transaminase - Yang, Ju Dong; Dai, Jianliang; Singal, Amit G; Gopal, Purva; Addissie, Benyam D; Nguyen, Mindie H; Befeler, Alex S; Reddy, K Rajender; Schwartz, Myron; Harnois, Denise M; Yamada, Hiroyuki; Gores, Gregory J; et al. (Cancer epidemiology, biomarkers & prevention, 2017)
The utility of alpha-fetoprotein (AFP) for hepatocellular carcinoma (HCC) surveillance is controversial. We aimed to identify factors associated with elevated AFP and define the patients for whom AFP is effective for surveillance. Data from the NCI Early Detection Research Network phase II HCC biomarker study (233 early-stage HCC and 412 cirrhotic patients) were analyzed. We analyzed 110 early-stage HCC and 362 cirrhotic hepatitis C virus (HCV) patients for external validation. Sensitivity, specificity, and area under the ROC curve (AUC) for HCC were calculated. HCV etiology, non-White race, and serum alanine transaminase (ALT) predicted elevated AFP in cirrhotics. Non-White race and ALT predicted elevated AFP in HCC patients. Higher AUC of AFP for HCC was noted in patients with HBV (0.85) and alcohol (0.84), whereas it was lower in patients with hepatitis C virus (HCV; 0.80) and nonviral/alcohol etiology (0.76). The AUC was higher in HCV patients with serum ALT ≤40 U/L than patients with serum ALT >40 U/L (0.91 vs. 0.75, < 0.01). At 90% specificity, the sensitivity of AFP increased from 44% to 74% in Whites with HCV and from 50% to 85% in non-Whites with HCV. There was a trend toward higher AUC in HCV patients with serum ALT ≤40 U/L than those with serum ALT >40 U/L (0.79 vs. 0.69, = 0.10) in the validation cohort. The satisfactory performance of AFP in HCV patients with normal ALT should be further validated. The AFP may serve as a valuable surveillance test in HCV patients with normal ALT. .